Emulsion copolymerization of vinyl acetate and 2-ethyl hexyl acrylate using nonionic emulsifiers in loop reactor - Sarac, A; Keklik, M; Yidiz, Ö; Yidirim, H (JOHN WILEY & SONS INC, 2005)
Batch emulsion copolymerization of vinyl acetate and 2-ethyl hexyl acrylate (VAc/2EHA = 90: 10) was initiated by the thermal initiators ammonium persulfate and potassium persulfate at 70 degrees C in the presence of nonylphenol ethoxylates with varying chain lengths and poly(vinyl alcohol). VAc-2EHA copolymer latexes were synthesized as two different series in a loop reactor. The first series was initiated by ammonium persulfate, and the second series was initiated by potassium persulfate. The influence of the counterions or initiators and chain lengths of a nonionic emulsifier on the properties of VAc-2EHA copolymer latexes were determined by measuring the viscosities, weight-average molecular weights, number-average molecular weights, molecular weight distribution, and surface tension of latexes to air. The results for the copolymer latexes indicated that some of their physicochemical properties increased with increasing chain length of the nonionic emulsifier, but some of them followed a different trend for the two initiators. (c) 2005 Wiley Periodicals, Inc.
Keywords: vinyl acetate; 2-ethyl hexyl acrylate; emulsion polymerization; degree of ethoxylation; BUTYL ACRYLATE; ETHOXYLATION DEGREE; CO-POLYMERIZATION; SURFACTANTS; LATEXES; BATCH; Polymer Science